Reference values for respiratory events in overnight polygraphy from infants aged 1 and 3 months - Brockmann, Pablo E; Poets, Anette; Poets, Christian F (Sleep medicine, 2013)
Highlights • Standards for analyzing sleep studies have not included young infants to date. • We provide reference values for cardiorespiratory variables in infants aged 1 and 3 months. • Some current adult-derived event definitions should be questioned based on these data.